Belgium in UFO Photographs, Volume 1 (1950-1988), FOTOCAT Report #7 by Vicente-Juan Ballester Olmos & Wim van Utrecht - Shough, Martin (Journal of Scientific Exploration, 2018)
Both authors of this important book, Vicente-Juan Ballester-Olmos and Wim Van Utrecht, are well known and highly regarded in the field of ufology for the solid work they have done over decades. Van Utrecht has conducted many field investigations, co-founded an ongoing report-monitoring operation in Belgium (Belgisch UFO-meldpunt) and notably is the architect and custodian of the mighty CAELESTIA online research resource. Ballester Olmos has authored hundreds of articles and books, almost single-handedly mediated the declassification of Spanish Air Force UFO archives in the 1990s, and today maintains the colossal FOTOCAT Project database which is the foundation of this book. BELGIUM IN UFO PHOTOGRAPHS is the first of a pair of volumes which together will form an exhaustive history of Belgian UFO photography from its inception. A chronological catalogue of individual cases (84 in this volume) is followed by statistical breakdowns and some discussion of the quality and meaning of the evidence. As the authors immediately acknowledge, most readers will dismiss the majority of UFO photographs out of hand as merely plates and frisbees, birds, lens flares, stars and the like. But they take nothing for granted: The million-dollar question, of course, is to know if there are any images left that are not explainable as hoaxes or misinterpretations? It is the main goal of our project to find that out. Volume 1 covers the years 1950-1988. Part 1 occupies the bulk of the book and contains the catalogue of events, divided into three chapters: Chapter 1, 1950-1971 ‘When UFOs Were Still Flying Saucers’; Chapter 2, 1972-1980 ‘Sightings Peak’; and Chapter 3, 1981-1988, ‘Calm Before the Storm’. Part 2, ‘Reviewing the Data’, contains Chapter 4, 1950-1988, ‘Statistics and Conclusions’. There are 413 pages in total including Contents, Dedication, a Foreword by James Oberg, Bibliography, List of Acronyms, Acknowledgments, and an Appendix listing all the columns and codes in the FOTOCAT database spreadsheet.